An algorithm of rehabilitation examination of persons with Charcot-Marie-Toot disease - Iryna Korman (Kharkiv State Academy of Physical Culture, 2017)
The Charcot-Marie-Toot disease is a hereditary demyelinated polyneuropathies, accompanied by a complex of physical and functional disorders from the musculoskeletal and nervous systems. Purpose: to develop an algorithm for the rehabilitation examination of persons with Charcot-Marie-Toot's disease. Material & Methods: theoretical analysis and generalization of data from scientific and methodological literature and the worldwide Internet information network, classification. Result: algorithm of rehabilitation examination is offered that will allow fully covering the existing violations and objectively assessing the physical and functional state of the patient for this disease is proposed. Conclusion: carrying out a comprehensive rehabilitation survey and analyzing its results is the basis for an adequate selection of means and methods of physical rehabilitation and building a rehabilitation intervention plan.